PET/CT fusion in radiotherapy planning for lung cancer - case reports - Erak Marko Đ.; Mitrić Milana; Đuran Branislav; Tešanović Dušanka; Vasiljev Sanja (Vojnosanitetski Pregled)
Introduction. Application of imaging methods, namely computed tomography (CT), magnetic resonance imaging (MRI) and in recent years positron emission tomography-computed tomography (PET/CT), and the progress of computer technology have allowed the construction of effective computerized systems for treatment planning (TPS) and introducing the concept of virtual simulation in 3D conformal radiotherapy planning. Case report. We hereby presented two patients with the diagnosis of non-small cell lung cancer who did PET/CT examination. Both patients had surgery earlier and local recidives are diagnosed with PET/CT. PET/CT of the first patient described the focus of intense fluorodeoxyglucose (FDG) accumulation 2.99 × 2.9 × 2.1cm in diameter in the projection of soft-tissue volume in the left corner, at operating clips height, corresponding to metabolically active recurrence of the tumor. Mediastinum and right lung parenchyma were without focal accumulation of FDG. Control PET/CT after 3 months was without detectable focus of intense pathological FDG accumulation - good therapeutic response, (metabolic disease remission). On the other hand, in the second case PET/CT showed a focus of intense FDG accumulation screening in the scar tissue of the apical part of the right lung, 20 × 16 mm, corresponding to metabolically active tumor recurrence. In the lung parenchyma on the left and in the mediastinum no visible focus of intense FDG accumulation was descrbed. Radiography included using 3D conformal radiotherapy with fusion PET/CT scan and CT simulations. Conclusion. PET/CT provides important information for planning conformal radiotherapy, especially in dose escalation, sparing of organ at risk and better locoregional control of the disease.